Radiation heart disease in a patient post treatment of Нodgkin’s lymphoma - Е. S. Eniseeva; К. V. Protasov; N. L. Chernysheva; E. Yu. Bagadaeva; A. A. Stefanenkova (Российский кардиологический журнал)
A clinical case of radiation induced heart disease in 43 year old female patient after 15 years since radiation therapy of Hodgkin’s lymphoma. During clinical and instrumental investigation, a post-radiation constrictive pericarditis was found, comorbid with lesion of aortic, mitral and tricuspid valves. Surgical treatment of pericarditis was applied. Morphology confirmed the diagnosis.